Design and Development of an Oil Palm Fresh Fruit Bunch Cutting Device - Jelani, Abdul Razak (1997)
A study was conducted with the objective to investigate the effect of cutter design, cutting angle and frond maturity on specific cutting force and energy requirement per unit cut area for cutting oil palm fronds. Two designs were tested, that is sickle cutter and claw cutter. Cutting angles were studied at 90°, 60° and 45°, while three levels of frond maturities were used as test samples. The experiment conducted showed significant effect of cutter design, cutting angle, frond maturity and the interaction of cutter design and cutting angle on specific cutting force (FOCSA) and energy (ENCSA) requirement for cutting oil palm fronds. The maximum FOCSA for sickle and claw cutter were 12.18 kg/cm2 and 22.9 kg/cm2 respectively, while the maximum ENCSA for sickle and claw cutter were 65.41 kg-cm/ cm2 and 115.5 kg-cm/cm2 respectively. This indicated that sickle cutter required 88% less FOCSA and 76.5% less ENCSA to that of claw cutter. It was found that increasing the cutting angle would result in higher FOCSA and ENCSA requirements. The trend was found similar to frond maturity in that the mature the frond, the higher the FOCSA and ENCSA required to accomplish the cutting. Another experiment using a spring activated sickle cutter (without countershear) to investigate the effect of cutting angle and frond maturity on specific reaction force and energy requirement for cutting oil palm fronds was carried out. This experiment was conducted to determine the reaction force that would be transferred to the harvester in the cutting operation. The experiment carried out showed significant effect of cutting angle on specific reaction force (ROC SA) and energy (RENCSA) but not on the frond maturity. Increasing the cutting angle from 45° to 9<F would Increase the ROCSA to about 72%. The maximum and minimum value of ROCSA were 2.5 kg/cm2 and 1.1 kg/cm2 respectively. Cutting angle and frond maturity were found to significantly affect the R/F Cmax (the ratio of reaction force to maximum cutting force). The maximum and minimum ratio were 35% and 14% at cutting angle of 70° and 4S for cutting F3 and FI respectively. A prototype spring activated sickle cutter was then developed based on information obtained from the experiments. The prototype was field tested in which a time and motion study to cut fronds as well as fruit bunches was carried out. Test conducted revealed that the cutter could cut a frond and a fruit bunch in 20.08 s and 7.2 s respectively. On average the cutter needed three strokes to accomplish a cutting due to insufficient length of spring. Therefore, in future, some improvements and modifications should be made on its spring design so as to increase its efficiency.